2013
DOI: 10.2166/wrd.2013.048
|View full text |Cite
|
Sign up to set email alerts
|

Investigating psychological factors of behavioural intention of urban residents in South Australia to use treated stormwater for non-potable purposes

Abstract: This paper reports on the intentions of urban residents in two South Australian Local Government Areas (LGAs) (council areas) to use stormwater treated through a managed aquifer recharge process for various potential non-potable uses. Data were collected through an online survey of the residents in these LGAs. The key finding is that, in common with recycled sewage water, the intention to use treated stormwater was lower for uses having closer contact with people. A hypothesized model consisting of possible fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 7 publications
4
14
1
Order By: Relevance
“…In the context of recy stormwater meeting the necessary water quality standards in Taiyuan City, perce health risks were found not significantly impacting residents' intention to accept u the water. The finding supports the earlier study by the Australian Federal Scientific Industrial Research Organization (CSIRO) [38]; while is inconsistent with that of Dol and Grunand [19] or Wu et al [6] that found perceived health risks can affect resid intention to use the recycled stormwater. The study of Dolnicar and Grun [19], Wu et al [33] or Mankad et al [11] were all conducted in Australia.…”
Section: Resultscontrasting
confidence: 62%
“…In the context of recy stormwater meeting the necessary water quality standards in Taiyuan City, perce health risks were found not significantly impacting residents' intention to accept u the water. The finding supports the earlier study by the Australian Federal Scientific Industrial Research Organization (CSIRO) [38]; while is inconsistent with that of Dol and Grunand [19] or Wu et al [6] that found perceived health risks can affect resid intention to use the recycled stormwater. The study of Dolnicar and Grun [19], Wu et al [33] or Mankad et al [11] were all conducted in Australia.…”
Section: Resultscontrasting
confidence: 62%
“…Detailed information about types of questions and response format that we have used are detailed in [21] and [28].…”
Section: Resultsmentioning
confidence: 99%
“…Table 3 reports the frequencies only and the factors influencing Salisbury residents to uptake the stormwater treated through MAR process for different uses were explored and reported in our recent work [28]. The factors influencing Salisbury residents to take up the stormwater treated through the MAR process for different uses were explored and reported upon in Table 3.…”
Section: Mar (Managed Aquifer Recharge)mentioning
confidence: 99%
“…Typically, in urban Australia, the public has felt uninformed about urban water decisions and has demonstrated low uptake of urban water initiatives. Yet the role of trust relevant to storm water has been somewhat different to that of other alternative sources and, instead, has been associated with lower perceived risks associated with the water source [ Wu et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…'s [] and Wu et al . [] works, public trust is also central to the issue of acceptance for storm water technology and storm water reuse. The importance of trust in the context of storm water is consistent with much of the past research on other types of alternative water sources such as desalination, rainwater, and recycled wastewater [e.g., Hurlimann , ; Mankad and Tucker , ; Nancarrow et al ., ].…”
Section: Introductionmentioning
confidence: 99%